The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms222212094
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genetic Dysregulations and Oxidative Damage in Fusarium graminearum Induced by Plant Defense Eliciting Psychrophilic Bacillus atrophaeus TS1

Abstract: This study elaborates inter-kingdom signaling mechanisms, presenting a sustainable and eco-friendly approach to combat biotic as well as abiotic stress in wheat. Fusarium graminearum is a devastating pathogen causing head and seedling blight in wheat, leading to huge yield and economic losses. Psychrophilic Bacillus atrophaeus strain TS1 was found as a potential biocontrol agent for suppression of F. graminearum under low temperature by carrying out extensive biochemical and molecular studies in comparison wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 89 publications
1
19
0
Order By: Relevance
“…Similar to our study, a significant decrease in disease development in Bacillus treated cotton plants compared to control has been reported 41 . Previously, B. atrophaeus TS1 suppressed the infection of F. graminearum on wheat 50 . However, B. thuringiensis CHGP12 also showed an increase in total biomass of the chickpea plant indicating the dual role of CHGP12 in controlling the infection and promoting plant growth.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to our study, a significant decrease in disease development in Bacillus treated cotton plants compared to control has been reported 41 . Previously, B. atrophaeus TS1 suppressed the infection of F. graminearum on wheat 50 . However, B. thuringiensis CHGP12 also showed an increase in total biomass of the chickpea plant indicating the dual role of CHGP12 in controlling the infection and promoting plant growth.…”
Section: Discussionsupporting
confidence: 89%
“…The hydrolytic enzymes produced by Bacillus species perform a dual role as they are not only involved in causing the direct lysis of the cell wall of fungi, but they can also improve the plant growth. In a similar study, it was reported that the inhibition of F. graminearum by B. atrophaeus TS1 was due to the production of hydrolytic enzymes 50 . These hydrolytic enzymes deliver energy to the germinating plants by solubilizing endospermic food stored in the food such as starch, lipid, and proteins 51 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the excessive use of chemical pesticides has resulted in environmental pollution, thereby limiting their use in the agricultural sector [ 3 , 4 ]. Currently, researchers are exploring the use of beneficial microorganisms as an eco-friendly strategy to control crop diseases [ 3 , 5 ]. A diverse range of bacterial genera have demonstrated great potential as biocontrol agents for various plant diseases.…”
Section: Introductionmentioning
confidence: 99%